Inflorescence temperature influences fruit set, phenology, and sink strength of Cabernet Sauvignon grape berries - Keller, Markus; Scheele-Baldinger, Regula; Ferguson, John C.; Tarara, Julie M.; Mills, Lynn J. (Frontiers in Plant Science, 2022)
The temperature during the bloom period leading up to fruit set is a key determinant of reproductive success in plants and of harvest yield in crop plants. However, it is often unclear whether differences in yield components result from temperature effects on the whole plant or specifically on the flower or fruit sinks. We used a forced-convection, free-air cooling and heating system to manipulate the inflorescence temperature of field-grown Cabernet Sauvignon grapevines during the bloom period. Temperature regimes included cooling (ambient – 7.5°C), heating (ambient + 7.5°C), an ambient control, and a convective control. Cooling significantly retarded the time to fruit set and subsequent berry development, and heating shortened the time to fruit set and accelerated berry development relative to the two controls. Fruit set was decreased in cooled inflorescences, but although the cooling regime resulted in the lowest berry number per cluster, it also decreased seed and berry weight at harvest while not affecting seed number. Cooling inflorescences slightly decreased fruit soluble solids and pH, and increased titratable acidity, but did not affect color density. The inflorescence temperature did not impact leaf gas exchange and shoot growth, and shoot periderm formation occurred independently of the timing of fruit ripening. The present results indicate that fruit set and subsequent seed and berry development in grapevines depend on the temperature experienced by the flowers during bloom time. Suboptimal temperatures not only reduce the proportion of flowers that set fruit but also limit the sink strength of the berries that do develop after fruit set. Shoot vigor and maturation, and leaf physiology, on the other hand, may be rather insensitive to temperature-induced changes in reproductive development.